Spaces, voices, and acting: Mapping of the “Fantastique” filmed in Madrid - Fernández-Hoya, Gema (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this research is to study the film tourism project "Comunidad de Madrid Fantastic” and examines the possible interest that this initiative has generated, the different filmic discourses of the Fantastique and its characters. A methodology is developed in two phases: the analysis of the aforementioned project, together with a quantitative correlational investigation based on the data provided by Film Madrid and the investigation using the Google Trends tool on searches for spaces linked to gender in the CAM. The results show a valuable film-tourism proposal that arouses interest, but fails to mobilize citizens towards the proposed destinations.